A systematic review of the anatomical findings of multiple gallbladders. Issue 11 (November 2018) - Darnis, Benjamin; Mohkam, Kayvan; Cauchy, François; Cazauran, Jean-Baptiste; Bancel, Brigitte; Rode, Agnès; Ducerf, Christian; Lesurtel, Mickaël; Mabrut, Jean-Yves
Abstract: Background: Multiple gallbladders (MG) are a rare malformation, with no clear data on its clinical impact, therapeutic indications or risk for malignancy. Methods: A systematic review of all published literature between 1990 and 2017 was performed using the PRISMA guidelines. Results: Data of 181 patients extracted from 153 studies were reviewed. MG were diagnosed during the treatment of a gallstone-related disease in 83% of patients, of which 13% had previous cholecystectomy and had a recurrence of biliary stone disease. The sensitivity of ultrasound scan was 66%, and that of magnetic resonance imaging cholangio-pancreatography, 97%. The cystic duct was common to both gallbladders (type1) in 43% and separated (type 2) in 50% of patients. In the latter case, there was no way to differentiate preoperatively an accessory gallbladder from a Todani II bile duct cyst. Cholecystectomy was performed in 129 patients by laparotomy (43%) or laparoscopy (56%). MG was undiagnosed before surgery in 24% of the patients. The postoperative biliary leakage rate was 0.7%. In two patients, gallbladder cancers were detected. Conclusion: MG are difficult to diagnose and share a common natural history with single gallbladders, without evidence of increased risk for malignancy. Excision of both gallbladders is indicated in symptomatic stone disease. However, prophylactic cholecystectomy must be considered for type 2 MG, since it cannot be preoperatively differentiated from a Todani II bile duct cyst, which is associated with a risk of malignant transformation.